Structural convergence and membrane interactions of Aβ1-42 along the primary nucleation process studied by solid state NMR - Maurine K. Kengwerere; June M. Kenyaga; Peng Xiao; Shubha S. Gunaga; Faith J. Scott; Xyomara Wutoh-Hughes; James Wang; Brian Lum; Yan Sun; Frederic Mentink-Vigier; Tuo Wang; Wei Qiang (Communications Chemistry)
Abstract Non-specific disruption of cellular membranes induced by amyloidogenic aggregation of β-amyloid (Aβ) peptides remains a viable cytotoxicity mechanism in Alzheimer’s disease (AD). Obtaining structural information about the intermediate states of Aβ-membrane systems and their molecular interactions is challenging due to their heterogeneity and low abundance. Here, we systematically study the molecular interactions of membrane-associated Aβ1-42 peptides using solid-state nuclear magnetic resonance (ssNMR) spectroscopy, focusing on the primary nucleation phase of the fibrillation process. Compared to the less pathogenic Aβ1-40 peptide, Aβ1-42 forms smaller oligomers prior to fibrillation, as evidenced by a higher overall population of lipid-proximity peptides. Aβ1-42 also exhibits more pronounced residue-specific contacts with phospholipid headgroups compared to Aβ1-40, with multiple lipid-proximity segments throughout the entire primary sequence. The segments involved in initial inter-strand assembly overlap with those located near the lipid headgroups in Aβ1-42, whereas these two segments are distinct in Aβ1-40. ssNMR spectroscopy with sensitivity enhanced by Dynamic nuclear polarization (DNP) confirmed local secondary structural convergence during the nucleation process of Aβ1-42 and the presence of long-range tertiary contacts at early stages of nucleation. Overall, our results provide a molecular-level understanding of the Aβ1-42 nucleation process in a membrane-like environment and its membrane-disrupting intermediates. The comparison between Aβ1-42 and Aβ1-40 explains its higher cytotoxicity from the perspective of membrane disruption.